2018
DOI: 10.1038/s41598-018-35847-w
|View full text |Cite
|
Sign up to set email alerts
|

The LPG1x family from Leishmania major is constituted of rare eukaryotic galactofuranosyltransferases with unprecedented catalytic properties

Abstract: Galactofuranosyltransferases are poorly described enzymes despite their crucial role in the virulence and the pathogenicity of numerous microorganisms. These enzymes are considered as potential targets for therapeutic action. In addition to the only well-characterised prokaryotic GlfT2 from Mycobacterium tuberculosis, four putative genes in Leishmania major were previously described as potential galactofuranosyltransferases. In this study, we have cloned, over-expressed, purified and fully determined the kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…[1] However, under its furanose form, galactofuranose (Galf) is totally absent from mammals, but is present in many pathogenic microorganisms. [2] , [3] Indeed, there are three main and specific enzymes involved in the biosynthesis and the metabolism of the Galfcontaining molecules [4]: UDP-galactopyranose mutase (UGM), [5] galactofuranosyltransferase (GalfT) [6] and galactofuranosidase (Galf-ase). [7] The glycobiology of Galf and enzymes involved in its metabolism have thus become attractive targets for the development of antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…[1] However, under its furanose form, galactofuranose (Galf) is totally absent from mammals, but is present in many pathogenic microorganisms. [2] , [3] Indeed, there are three main and specific enzymes involved in the biosynthesis and the metabolism of the Galfcontaining molecules [4]: UDP-galactopyranose mutase (UGM), [5] galactofuranosyltransferase (GalfT) [6] and galactofuranosidase (Galf-ase). [7] The glycobiology of Galf and enzymes involved in its metabolism have thus become attractive targets for the development of antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, LPG1 from Leishmania major was the first and only described eukaryotic Galf T. In an extensive study from 2018, all the four putative transferases (LPG1, LPG1G, LPG1L and LPG1R) encoded in the L. major genome were cloned, overexpressed and their kinetic parameters determined. It was demonstrated that they are able to use both UDP-Galf and UDP-Galp as donor substrates [42].…”
Section: Galactofuranosyltransferase (Galft)mentioning
confidence: 99%